Organic Bovine Graft Associated With PRP In Rabbit Calvaria - Rocha, Flaviana Soares; Ramos, Lara Maria Alencar; Batista, Jonas Dantas; Zanetta-Barbosa, Darceny; Dechichi, Paula (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Repairing large bone defects is a huge challenge that reconstructive surgery currently faces.Objective: The objective of this study was to perform the histological evaluation of bone repair in rabbit calvaria when using bovine bone graft (Gen-ox-organic®) associated with platelet-rich plasma (PRP).Method: 12 rabbits were used and two bone fragments were bilaterally removed from calvaria. Then, 24 surgical sites were randomly divided into 3 groups: coagulum (group I), organic (group II) and PRP-included organic (group III). After four weeks, the animals were sacrificed and the grafted area removed, fixed in 10% formalin with PBS 0.1 M, and embedded in paraffin.Study method: The analyzed histological parameters were: defective area filled with the newly-formed bone, graft's giant cells and particles, as well as the new bone formation associated with the particles. Group I's defects were filled with fibrous tissue attaching the periosteum and revealed a little bone formation peripherally. In both groups II and III, a similar standard was noticed in addition to the absence of graft particles and giant cells. There was no significant difference in the number of giant cells, graft particles and new bone formation around the particles between the grafted material and the PRP-related group.Conclusion: The results achieved indicate that the organic biomaterial neither separately nor jointly with PRP improves bone regeneration.
Keywords: bone regeneration; platelet-rich plasma; organic compounds